Features of the motivational profile of police officers’ personality - O. M. Smirnova (Law and Safety)
On the basis of the analysis of a significant number of domestic and international theoretical and research works, where professional motivation has been researched; the author has formed own definition of the concept of the motivational profile of an employee of the National Police of Ukraine, where the author suggests to understand the totality of internal and external motive forces, which induce an employee to the productive activity to achieve personal goals and the main objective of the unit, as well as specify the boundaries and forms of activity and add to this activity the tendency oriented towards the achievement of defined goals.